Calanoid copepods of the Province of La Pampa (Semiárida, 2020)
The aim of this work 15 to identify the calanoid copepods of different water bodies of the province of la Pampa. 78 samples were taken from permanent and non-permanent environments. Boeckella gracilis, B. poopoensis and Notodiaptomus incompositus were identified. A diagnosis o, the species and hydrology, pH, salinity, Secchi transparency of the ponds are given.
Keywords: copepods; calanoids; La Pampa